Multi-level impact of continuing professional development on Sri Lanka's veterinary sector. (2nd January 2023) - Kinnison, Tierney; Thuranira-McKeever, Christine; Kalupahana, Ruwani; Silva-Fletcher, Ayona
ABSTRACT: A capacity-building programme between a veterinary school in the UK and the veterinary school in Sri Lanka was developed. Scholarships for two distance learning MSc programmes were offered to Sri Lankan veterinarians: 'Veterinary Epidemiology and Public Health' and 'Livestock Health and Production'. In addition, scholarships were offered to academic staff members at the veterinary school to undertake the Postgraduate Certificate in Veterinary Education. A blended learning approach was taken, though the majority of learning was by distance. This study used a case-study approach to assess the programmes' impact at different levels: individual, institutional, institution's students, the profession, the public and animals. Previous students were interviewed and current students participated in a focus group. Staff of the Sri Lankan university were interviewed. Data were transcribed and qualitative content analysis conducted. Participants had achieved personal satisfaction, gained new knowledge and skills and progressed professionally. These impacts translated to societal impacts including disseminating understanding of One Health, improving animal welfare laws and assisting the development of the undergraduate veterinary curriculum. The graduates from theblended learning programmes are experts at the centre of a new community of practice and have the ability to inspire future generations of Sri Lankan veterinary surgeons.